2019
DOI: 10.3390/w11040736
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of Microbial Communities Response to Shallow Groundwater Contamination in Typical Piedmont Region of Taihang Mountains in the North China Plain

Abstract: Regional-scale nitrate and organic contaminants in the shallow groundwater were investigated in the Piedmont region of Taihang Mountains (PRTM), but the information of the microbial communities is limited. However, microorganisms provide a dominated contribution to indicate and degrade the contaminants in the aquifer. Therefore, this study investigates the microbial diversity and contamination microbial indicators of groundwater samples with different contaminated types to better understand the contamination i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…This, partial 16S RNA gene amplicon sequencingbased study identified immense bacterial diversity in O'ahu's aquifers, which is comparable to, or even rivals the diversity found in surface soils. Average diversity estimates (Table 1) in Oahu aquifers, although not unusual for aquifer samples and heavily influenced by the analytical methods, appear to be elevated when compared to several studies [36][37][38] conducted in the continental aquifers. For example, in the studies referenced the average Shannon's diversity index remained below 4, while in our samples the average index averaged roughly 5.3.…”
Section: Discussionmentioning
confidence: 72%
“…This, partial 16S RNA gene amplicon sequencingbased study identified immense bacterial diversity in O'ahu's aquifers, which is comparable to, or even rivals the diversity found in surface soils. Average diversity estimates (Table 1) in Oahu aquifers, although not unusual for aquifer samples and heavily influenced by the analytical methods, appear to be elevated when compared to several studies [36][37][38] conducted in the continental aquifers. For example, in the studies referenced the average Shannon's diversity index remained below 4, while in our samples the average index averaged roughly 5.3.…”
Section: Discussionmentioning
confidence: 72%
“…A possible explanation can be the presence of LD12 bacteria in the groundwater aquifers, which sheds light on the existence of the SAR11 bacterial family in the groundwater communities, which has not previously been reported (Z. He et al, 2019;Sang et al, 2018).…”
Section: Ld12 Is a Keystone Organism In A Tropical Quarry Lake Systemmentioning
confidence: 81%